2005
DOI: 10.1007/s00468-005-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing photosynthetic efficiency in an experimental mangrove canopy using remote sensing and chlorophyll fluorescence

Abstract: This study examined the ability of the photochemical reflectance index (PRI) to track changes in effective quantum yield ( F/F m ), non-photochemical quenching (NPQ), and the xanthophyll cycle de-epoxidation (DPS) in an experimental mangrove canopy. PRI was correlated with ( F/F m ) and NPQ over the 4-week measurement period and over the diurnal cycle. The normalised difference vegetation index (NDVI) was not correlated with any aspect of photochemical efficiency measured using chlorophyll fluorescence or xant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 32 publications
7
27
0
Order By: Relevance
“…Some studies have demonstrated a strong correlation between PRI and NPQ (reviewed by Garbulsky et al [4]), but our measurements indicated a poorer performance of PRI in tracking NPQ over longer periods, which is similar to results of Nichol et al [7] and Rahimzadeh-Bajgiran et al [50]. Porcar-Castell et al [56] attributed disruptions in the relationship between PRI and NPQ to differences in the physiological mechanisms controlling each variable and to other forms of energy dissipation independent of the xanthophyll cycle, particularly at low temperatures.…”
Section: Use Of ∆Pri For Tracking Photosynthetic Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…Some studies have demonstrated a strong correlation between PRI and NPQ (reviewed by Garbulsky et al [4]), but our measurements indicated a poorer performance of PRI in tracking NPQ over longer periods, which is similar to results of Nichol et al [7] and Rahimzadeh-Bajgiran et al [50]. Porcar-Castell et al [56] attributed disruptions in the relationship between PRI and NPQ to differences in the physiological mechanisms controlling each variable and to other forms of energy dissipation independent of the xanthophyll cycle, particularly at low temperatures.…”
Section: Use Of ∆Pri For Tracking Photosynthetic Performancesupporting
confidence: 90%
“…Regression analysis connecting data measured across all irradiation and temperature conditions (n = 45) showed the closest association of PRI with leaf Φ PSII (Figures 9 and 10), which concurs with results provided by other authors [7,39,49,50]. However, the tight relationship between Φ PSII , LUE, and PRI may exist only under non-stressed conditions [51], typically observed under low light intensities.…”
Section: Use Of Pri For Determining Photosynthetic Parameterssupporting
confidence: 89%
“…Diurnal changes in PRI were already shown to be related to diurnal adaptation of photosynthesis [53]. F 760 is emitted from the core of both photosystems and, thus, is related to the efficiency of photochemical energy separation.…”
Section: Discussionmentioning
confidence: 96%
“…The PRI, in contrast, is related to the degree of non-photochemical energy dissipation (NPQ). F 760 and PRI are often inversely correlated (e.g., [53,54]). However, it cannot be assumed that they are simply or linearly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PRI is an index that was first formulated as an indicator of photosynthetic efficiency, but is also an indicator of photosynthesis rate through light use efficiency (Asner et al, 2005;Drolet et al, 2005;Fuentes et al, 2006;Guo & Trotter, 2004;Nakaji et al, 2006;Nichol et al, 2000Nichol et al, , 2002Serrano & Peñuelas, 2005;Sims et al, 2006;Strachan et al, 2002;Trotter et al, 2002) and through chlorophyll fluorescence (Dobrowsky et al, 2005;Evain et al, 2004;Nichol et al, 2006). Therefore, PRI in addition to being a water stress indicator, is also directly related to several physiological processes involved in the photosynthetic system.…”
Section: Introductionmentioning
confidence: 99%